Adaptation of the ILO-WHO Workplace Stress Scale in workers from 25 to 35 years of age in a Contact Center in Lima Center in Lima - Suárez Tunanñaña, Ángela (2013)
Stress Scale of the OIT-OMS was adapted. In a sample of 203 employees who work as telephone assistant, among which 89 are in the Customer Service area and 114 in the area of a Sales Contact Center of Lima. The results indicate that the the Job Stress Scale gets adequate psychometric properties: Reliability through the method of internal consistency (Cronbach´s alpha = 0.972) and construct validity. Finally, the scales were performed in the total sample.